A process for producing biological control agent - Lau , Wei Hong; Abdul Samad, Noraini; Sajap, Ahmad Said; Abdul Kadir, Hussan (2010)

(untitled)
Present presentation relates to a method for producing nucleopolyhedrovirus as a biological control agent for armyworm. The method according to the present invention comprising in vitro production of nucleopolyhedrovirus in S. litura larvae, isolation and purification of the S. litura diseased larvae, followed by bioassay and identification of the said biological control agent. The mortality of the infected larvae increased with increasing dosage of SpltNPV isolated from S. litura diseased larvae. A higher dosage also leads to a more rapid effect of polyhedrosis.